Walk 2 remember : tackling dementia together, one step at a time - Tee, Bertrand Zhi Ying (2019)
Walk 2 Remember is a pioneering health communications campaign that aimed to promote intergenerational walking behaviours amongst Singaporean adults and the senior relatives they live with in a bid to combat dementia in Singapore, a rapidly ageing society. While there is no known cure for dementia, recent neurological studies have shown that the simple act of walking lowers the risk and/or progression of dementia. This knowledge underpinned this student-led initiative by four undergraduates from the Wee Kim Wee School of Communication and Information, Nanyang Technological University. As of 2018, one in 10 Singaporeans above 60 years old have dementia, with this prevalence increasing with age – one of dementia’s strongest risk factors. Walk 2 Remember tackled this through encouraging intergenerational walking habits, which encapsulated the social benefits of dementia management alongside walking’s. Guided by the Integrated Model of Behavioural Prediction, this campaign sought to impact 40 to 64 years old caregivers of cohabitant senior relatives, and managed to educate them on the cognitive benefits of walking while increasing the overall levels of intention and behaviour of walking with senior relatives. Qualitative and quantitative formative research informed the campaign’s strategic pillars – ‘Elevate’, ‘Educate’ and ‘Empower’ – which yielded a positive result in its effectiveness while also achieving more than S$700,000 in public relations value. This paper details the campaign’s process – from its formative phases to its strategic development, execution, and evaluation through a post-campaign survey. Finally, recommendations were also incorporated through the insights gleaned for future campaigners.